4-Carbamoylpiperidinium 2-carboxybenzoate–benzene-1,2-dicarboxylic acid (1/1) - Smith, Graham (International Union of Crystallography, 2011)
The asymmetric unit of the title salt adduct, C(6)H(13)N(2)O(+)·C(8)H(5)O(4) (−)·C(8)H(6)O(4), comprises one isonipecotamide cation, a hydrogen phthalate anion and a phthalic acid adduct molecule. These form a two-dimensional hydrogen-bonded network through head-to-tail cation–anion–adduct molecule interactions which include a cyclic heteromolecular amide–carboxylate motif [graph set R (2) (2)(8)], conjoint cyclic R (2) (2)(6) and R (3) (3)(10) piperidinium N—H⋯O(carboxyl) associations, as well as strong carboxyl O—H⋯O(carboxyl) hydrogen bonds.